2008
DOI: 10.1016/j.nutres.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and vitamin D intakes may be positively associated with brain lesions in depressed and nondepressed elders

Abstract: Studies indicate that diet and vascular calcification may be related to the occurrence of brain lesions, although the importance of dietary calcium and vitamin D has not been investigated. The objective of this study was to test the hypothesis that calcium and vitamin D intakes would be positively associated with brain lesion volumes in elderly individuals with and without late-life depression. A cross sectional study was performed as part of a longitudinal clinical study of late-life depression. Calcium and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 53 publications
1
29
1
2
Order By: Relevance
“…(44) The effect of dietary calcium intake on vascular calcification has not been reported for individuals with normal renal function, but epidemiologic studies have suggested that high calcium intakes are associated with a lower prevalence of vascular disease. (45)(46)(47)(48)(49) However, high calcium intakes have been associated with ischemic brain lesions on MRI (50) and with vascular calcification in populations with renal failure. (7,51,52) Our finding of decreased AAC in the highest quartile of dietary calcium intake is consistent with the epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…(44) The effect of dietary calcium intake on vascular calcification has not been reported for individuals with normal renal function, but epidemiologic studies have suggested that high calcium intakes are associated with a lower prevalence of vascular disease. (45)(46)(47)(48)(49) However, high calcium intakes have been associated with ischemic brain lesions on MRI (50) and with vascular calcification in populations with renal failure. (7,51,52) Our finding of decreased AAC in the highest quartile of dietary calcium intake is consistent with the epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…25 High calcium intakes have also been associated with brain lesions on magnetic resonance imaging scans 26 and with vascular calcification [27][28][29][30] and mortality 31 32 in patients who receive dialysis. Data from patients requiring dialysis may be relevant to the present study population because of the age of our participants and the associated reduced renal function.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Vitamin D 3 in its actions as a neurosteroid has been found to have neuroprotective properties comparable to those of the steroid estrogen in the treatment of some oxidative stress-related neurodegenerative disorders, but without estrogen's undesirable effects (Tetich et al 2003). There have been some fragmentary reports that vitamin D may play a less positive role as a neuroprotector (e.g., Payne et al 2008). But these reports are overwhelmed by the plethora of laboratory and human studies indicating that vitamin D combats neurodegenerative diseases.…”
Section: Vitamin D: Neuroprotectionmentioning
confidence: 99%